Polidocanol inhibits cowhage ‐ but not histamine‐induced itch in humans. Issue 12 (December 2014) - Hawro, Tomasz; Fluhr, Joachim W.; Mengeaud, Valérie; Redoulès, Daniel; Church, Martin K.; Maurer, Marcus; Metz, Martin
Abstract Polidocanol is a local anaesthetic and antipruritic compound that is used in the treatment of itching skin conditions such as eczema. Its mechanisms of action are largely ill defined. This study has compared the antipruritic efficacy of topical polidocanol in histamine‐induced itch and a histamine‐independent, cowhage‐induced model of pruritus. Polidocanol (3%) or vehicle was applied topically under occlusion for 1 h to the forearms of 45 healthy volunteers before itch was provoked by rubbing in 40–45 spicules of cowhage or skin prick testing with 10 mg/ml histamine. Itch was recorded at 1‐min intervals for 30 min on a 100‐mm visual analogue scale. Polidocanol significantly reduced the area under the curve for cowhage‐induced itch by 58% (P < 0.05), but had no significant effect on histamine‐induced itch. This result underlines the importance of histamine‐independent itch models in the development of topical antipruritic agents.